Annual memorial mass for deceased Lasallians - Suplido, Raymundo B., FSC (Animo Repository, 2020)
The Annual Memorial Mas remembered 41 souls, including 16 La Salle Brothers, who were massacred in the campus in the last days of the Japanese Occupation in 1945. Thirty-two beloved Lasallian students, faculty, staff, and alumni who passed away in 2019 were also remembered.